The 12-minute athlete get fitter, faster, and stronger using HIIT and your bodyweight - Stryker, Krista (Tiller Press, 2020)
"A practical guide to becoming stronger and unlocking your inner athletic potential through a mixture of HIIT and bodyweight workouts-all of which can be done in just minutes a day"--